The Forecasting of Net Electricity Consumption of the Consumer Groups in Turkey - ISIKAN, MUSTAFA OSMAN (TAYLOR & FRANCIS INC, 2011)
The main goal of this study is to reveal the future projections of net electricity consumption (NEC) as the consumer groups in Turkey by using the artificial neural network (ANN) technique. In this study the equations based on energy and economic indicators were obtained to predict the net electricity consumption as the consumer groups with high confidence to plan correct investments in Turkey. In this study, three different models were used in order to train the ANN. In Model 1, energy indicators such as installed capacity, generation, energy import and energy export were used as the input layer of the network. In Model 2, the sectoral share of Gross National Product (GNP) per capita was used. In Model 3, the sectoral share of Gross Domestic Product (GDP) per capita was used. The NEC of 25 different consumer groups are in the output layer for all models. The aim of using different models is to demonstrate the effect of sectoral share of economic indicators (GNP and GDP) on the estimation of NEC. R2 values are obtained similar to 1 for all models as consumer groups. Based on the output of the study, the ANN model can be used to estimate the NEC as the consumer groups from the energy and economic indicators.
Keywords: consumer; electricity; Turkey; SECTORAL ENERGY-CONSUMPTION; ARTIFICIAL-INTELLIGENCE; ECONOMIC-GROWTH; FUTURE; ALGORITHM; DEMAND; GDP